THE ISSUE OF ARTISTIC SOURCE AND LITERARY INFLUENCE IN THE LYRICS OF U. KHOJANAZAROV (Proceedings of International Conference on Modern Science and Scientific Studies, 2024)
In this scientific study, the issue of artistic source and literary influence in the lyrics of the renowned Karakalpak poet Ulmambet Khojanazarov is mentioned. It is clearly proven by examples, relying on reliable theoretical judgments.